(untitled) (Argos, 2017)
Christianity scholars recognize two great schools of thought –the Alexandrian and the Antiochian– which delineated the ideas that would serve as a structure for Christian theology. A point in discord between them was the allegorical exegesis of the Scriptures. Epiphanius, who supports the Antiochian trend of thought, condemns the allegorical method and, while presenting the reader with an exegetical proposal more in line with the orthodoxy, he includes Orígen among the sects treated in his Panarion. In our work we will analyze which are the required criteria proposed by the author to capture the true meaning of the biblical text.